Islamic Religious Education and Socio-Emotional Competency Development: A Case Study in an Elementary School - Kholil Chusyairi; Widodo Febri Utomo; Jumadi Jumadi (Al-Ilmu, 2024)
Islamic Religious Education (PAI) plays an important role in character building and the development of students' social-emotional competence in elementary schools. This study aims to explore the contribution of PAI in shaping students' social-emotional competence through the integration of religious values, such as empathy, compassion, and tolerance. Using a descriptive qualitative approach, this study involved 10 students, 5 PAI teachers, and 5 parents in an urban Islamic-based elementary school. Data were collected through in-depth interviews, classroom observations, and documentation, and then analyzed using thematic methods. The results showed that PAI teaching plays a significant role in improving students' social skills, such as the ability to cooperate, manage emotions, and resolve conflicts. PAI teachers as role models play an important role in this process, while faith-based extracurricular activities strengthen the application of social values such as discipline and empathy. Nonetheless, challenges in integrating religious values with students' social-emotional competencies include lack of family support, time constraints, and variations in understanding between teachers and students. This study recommends the need for more intensive teacher training as well as collaboration between schools, families, and communities to improve the effectiveness of PAI learning in developing students' social-emotional competencies.